Um ícone chamado PELÉ - Mauricio Murad (Caravelle)
This article analyzes the trajectory of Edson Arantes do Nascemento, better known as Pelé, as an icon of Brazilian culture, of its football, and even as a symbol of world football. It shows how Pelé, black and poor, managed to reach football’s highest level, the most popular and fascinating sport in the world. Pelé is the king of football, the century’s athlete. He is considered the most all-around player of all times, being a symbol of Brazilian identities and a reference player everywhere in the world.